Springboks at the Somme: The making of Delville Wood, 1916 - Nasson, Bill (My University, 1996)
In late-June 1916, Private James Ross of the 1st South African Infantry Brigade's 4th Regiment, South African Scottish, added a postscript to a letter despatched home to Cape Town from Sailly le Sec in the Picardy countryside. His mind and spirit instinctively forfeit to the green and tawny fields of northern France, ‘surely the neatest part of the globe’, he wrote to his parents, ‘what impresses me most here is the colour ... the red of the poppies is breathtaking, and truly indescribable.’ At this distance, Ross's observation seems almost a moment of providential suspension; until present and future merged, he seemed blithely unaware that the grassy realm around him was a poisoned pastoral. Near Corbie, further along the British Fourth Army's line, a resting fellow soldier, John Kilgour Parker, enjoyed a brisk sluicing in the Somme before idling away the 25th June, admiring the pipe bands of the 9th Division Black Watch or taking himself off to the sinewy challenge of tossing the caber against men of the 3rd Transvaal and Rhodesia Regiment. Aware of the incongruity of his tranquil reserve situation as the war closed in upon the recently-arrived South African contingent, Kilgour Parker was made edgy by the interminable din of the massive British artillery bombardment of German defences, reflecting, 'so much for this comic fireworks war. I suppose that if we took things seriously, our nerves would probably go in a month'. Yet things were very soon to be taken seriously, and men like Ross and Kilgour Parker would then find themselves advancing to the very border of their human sanity. For not far ahead lay the terrifying resolution of the Somme offensive, and in particular the perforating shock of Delville Wood for South African forces.
African Studies Seminar series. Paper presented 21 October 1996
Keywords: World War, 1914-1918. Regimental histories. South Africa